Chromosomal Region 11p14.1 is Associated with Pharmacokinetics and Pharmacodynamics of Bisoprolol - Fontana V; Turner RM; Francis B; Yin P; Pütz B; Hiltunen TP; Ruotsalainen S; Kontula KK; Müller-Myhsok B; Pirmohamed M (Dove Medical Press, 2022)
Vanessa Fontana,1,2 Richard Myles Turner,1,2 Ben Francis,3 Peng Yin,3 Benno Pütz,4 Timo P Hiltunen,5 Sanni Ruotsalainen,6 Kimmo K Kontula,5 Bertam Müller-Myhsok,1,4 Munir Pirmohamed1,2,7 1The Wolfson Centre for Personalised Medicine, Institute of Translational Medicine, University of Liverpool, Liverpool, UK; 2MRC Centre for Drug Safety Science, Department of Molecular and Clinical Pharmacology, University of Liverpool, Liverpool, UK; 3Department of Biostatistics, Institute of Translational Medicine, University of Liverpool, Liverpool, UK; 4Max Planck Institute of Psychiatry, Munich, Germany; 5Department of Medicine, University of Helsinki and Helsinki University Hospital, Helsinki, Finland; Research Program for Clinical and Molecular Metabolism, Faculty of Medicine, University of Helsinki, Helsinki, Finland; 6Institute for Molecular Medicine Finland, Helsinki Institute of Life Sciences, University of Helsinki, Helsinki, Finland; 7Royal Liverpool and Broadgreen University Hospitals NHS Trust, and Liverpool Health Partners, Liverpool, UKCorrespondence: Vanessa Fontana, MRC Centre for Drug Safety Science, Department of Molecular and Clinical Pharmacology, University of Liverpool, Block A: Waterhouse Buildings, 1-5 Brownlow Street, Liverpool, L69 3GL, UK, Fax +44 151 794 5059, Email V.Fontana@liverpool.ac.ukPurpose: Bisoprolol is a widely used beta-blocker in patients with cardiovascular diseases. As with other beta-blockers, there is variability in response to bisoprolol, but the underlying reasons for this have not been clearly elucidated. Our aim was to investigate genetic factors that affect bisoprolol pharmacokinetics (PK) and pharmacodynamics (PD), and potentially the clinical outcomes.Patients and Methods: Patients with non-ST elevation acute coronary syndrome were recruited prospectively on admission to hospital and followed up for up to 2 years. Patients from this cohort who were on treatment with bisoprolol, at any dose, had bisoprolol adherence data and a plasma sample, one month after discharge from index hospitalisation were included in the study. Individual bisoprolol clearance values were estimated using population pharmacokinetic modeling. Genome-wide association analysis after genotyping was undertaken using an Illumina HumanOmniExpressExome-8 v1.0 BeadChip array, while CYP2D6 copy number variations were determined by PCR techniques and phenotypes for CYP2D6 and CYP3A were inferred from the genotype. GWAS significant SNPs were analysed for heart rate response to bisoprolol in an independent cohort of hypertensive subjects.Results: Six hundred twenty-two patients on bisoprolol underwent both PK and genome wide analysis. The mean (IQR) of the estimated clearance in this population was 13.6 (10.0- 18.0) L/h. Bisoprolol clearance was associated with rs11029955 (p=7.17× 10− 9) mapped to the region of coiled-coil domain containing 34 region (CCDC34) on chromosome 11, and with rs116702638 (p=2.54× 10− 8). Each copy of the minor allele of rs11029955 was associated with 2.2 L/h increase in clearance. In an independent cohort of hypertensive subjects, rs11029955 was associated with 24-hour heart rate response to 4-week treatment with bisoprolol (p= 9.3× 10− 5), but not with rs116702638.Conclusion: A novel locus on the chromosomal region 11p14.1 was associated with bisoprolol clearance in a real-world cohort of patients and was validated in independent cohort with a pharmacodynamic association.Keywords: bisoprolol, pharmacokinetics, genome-wide association